2013
DOI: 10.1016/j.immuni.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

The Actin and Tetraspanin Networks Organize Receptor Nanoclusters to Regulate B Cell Receptor-Mediated Signaling

Abstract: A key role is emerging for the cytoskeleton in coordinating receptor signaling, although the underlying molecular requirements remain unclear. Here we show that cytoskeleton disruption triggered signaling requiring not only the B cell receptor (BCR), but also the coreceptor CD19 and tetraspanin CD81, thus providing a mechanism for signal amplification upon surface-bound antigen stimulation. By using superresolution microscopy, we demonstrated that endogenous IgM, IgD, and CD19 exhibited distinct nanoscale orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
401
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(451 citation statements)
references
References 46 publications
30
401
2
Order By: Relevance
“…The proportion of confined α6 integrin is decreased by 75% on a mammary cell line upon CD151 knockdown, consistent with the idea that CD151 clusters the integrin within nanodomains [48]. Furthermore, CD19 lateral diffusion is increased by 2.5-fold on B cells from CD81-knockout mice [47]. It is proposed that CD81 confines CD19 into nanoclusters that can interact with activated B-cell receptors to promote signalling [47].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The proportion of confined α6 integrin is decreased by 75% on a mammary cell line upon CD151 knockdown, consistent with the idea that CD151 clusters the integrin within nanodomains [48]. Furthermore, CD19 lateral diffusion is increased by 2.5-fold on B cells from CD81-knockout mice [47]. It is proposed that CD81 confines CD19 into nanoclusters that can interact with activated B-cell receptors to promote signalling [47].…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, CD19 lateral diffusion is increased by 2.5-fold on B cells from CD81-knockout mice [47]. It is proposed that CD81 confines CD19 into nanoclusters that can interact with activated B-cell receptors to promote signalling [47]. The mechanisms by which tetraspanins exert their effects on partner protein dynamics are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…On resting B cells, CD19 complex and the CD81‐tetraspanin complex are localized inside IgD‐class‐specific protein islands (Mattila et al , 2013; Maity et al , 2015). On activated B cells, however, the CD19 complex is found in close proximity to the open IgM‐BCR and thus gains access to ITAM signaling (Klasener et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that BCR microclusters function as a central platform for the signaling cascades that mediate B cell activation (3,16), which, in turn, are subject to the regulation imposed by CD19 and FcgRIIB. Batista and colleagues (17) were the first to report the key importance of BCR and CD19 microcluster colocalization in the initiation of BCR signaling, which has been advanced by their recent study using super-resolution microscopy to show the modestly concomitant concentration of BCR and CD19 molecules in Syk signaling microclusters upon BCR-Ag recognition (18).…”
mentioning
confidence: 99%